Gene Survey of the Pathogenic Protozoan Trypanosoma cruzi - Porcel, Betina M.; Tran, Anh-Nhi; Tammi, Martti; Nyarady, Zoltan; Rydåker, Maria; Urmenyi, Turan P.; Rondinelli, Edson; Pettersson, Ulf; Andersson, Bj̈orn; Åslund, Lena

(untitled) (Genome Research, 2000)
We have performed a survey of the active genes in the important human pathogen Trypanosoma cruzi by analyzing 5013 expressed sequence tags (ESTs) generated from a normalized epimastigote cDNA library. Clustering of all sequences resulted in 771 clusters, comprising 54% of the ESTs. In total, the ESTs corresponded to 3054 transcripts that might represent one-fourth of the total gene repertoire in T. cruzi. About 33% of the T. cruzitranscripts showed similarity to sequences in the public databases, and a large number of hitherto undiscovered genes predicted to be involved in transcription, cell cycle control, cell division, signal transduction, secretion, and metabolism were identified. More than 140 full-length gene sequences were derived from the ESTs. Comparisons with all open reading frames in yeast and in Caenorhabditis elegansshowed that only 12% of the T. cruzi transcripts were shared among diverse eukaryotic organisms. Comparison with other kinetoplastid sequences identified 237 orthologous genes that are shared between these evolutionarily divergent organisms. The generated data are a useful resource for further studies of the biology of the parasite and for development of new means to combat Chagas' disease.[The sequence data described in this paper have been submitted to the dbEST database under nos. TENU0001–TENU5214 and the following:AA736292-AA736301, AA738502-AA738535,AA756982-AA756992, AA835598-AA835613, AA866501-AA866550,AA87464-AA874780, AA875669-AA875730, AA875809-AA875824,AA879318-AA897341, AA879376-AA879401, AA882494-AA882518,AA883036-AA883051, AI005678-AI005729, AI007342-AI007441,AI021797-AI021884, AI026370-AI026615, AI037797-AI037846,AI043247-AI043343, AI043427-AI043502, AI046026-AI046290,AI050095-AI050219, AI053146-AI053397, AI057644-AI057957,AI065169-AI065425, AI066117-AI066391, AI069556-AI069908,AI073286-AI073332, AI075466-AI075620, AI077051-AI077281,AI078888-AI079000, AI080790-AI080916, AI083097-AI083245,AI110290-AI110405, AI110412-AI110512, AW324789-AW325325,AW329885-AW330435, and AW621062-AW621094. The sequences are also available at www.genpat.uu.se/tryp/tryp.html.]